Identification, Classification, and Growth of Moa Chicks (Aves: Dinornithiformes) from the Genus Euryapteryx - Huynen, Leon (Public Library of Science, 2014)

(untitled)
BACKGROUND: The analysis of growth in extinct organisms is difficult. The general lack of skeletal material from a range of developmental states precludes determination of growth characteristics. For New Zealand's extinct moa we have available to us a selection of rare femora at different developmental stages that have allowed a preliminary determination of the early growth of this giant flightless bird. We use a combination of femora morphometrics, ancient DNA, and isotope analysis to provide information on the identification, classification, and growth of extinct moa from the genus Euryapteryx. RESULTS: Using ancient DNA, we identify a number of moa chick bones for the species Euryapteryx curtus, Dinornis novaezealandiae, and Anomalopteryx didiformis, and the first chick bone for Pachyornis geranoides. Isotope analysis shows that ∂(15)N levels vary between the two known size classes of Euryapteryx, with the larger size class having reduced levels of ∂(15)N. A growth series for femora of the two size classes of Euryapteryx shows that early femora growth characteristics for both classes are almost identical. Morphometric, isotopic, and radiographic analysis of the smallest Euryapteryx bones suggests that one of these femora is from a freshly hatched moa at a very early stage of development. CONCLUSION: Using morphometric, isotopic, and ancient DNA analyses have allowed the determination of a number of characteristics of rare moa chick femora. For Euryapteryx the analyses suggest that the smaller sized class II Euryapteryx is identical in size and growth to the extant Darwin's rhea.